Immunotherapies targeting tumor vasculature: challenges and opportunities - Dianat-Moghadam, Hassan; Nedaeinia, Reza; Keshavarz, Mohsen; Azizi, Mehdi; Kazemi, Mohammad; Salehi, Rasoul (Frontiers in Immunology, 2023)
Angiogenesis is a hallmark of cancer biology, and neoadjuvant therapies targeting either tumor vasculature or VEGF signaling have been developed to treat solid malignant tumors. However, these therapies induce complete vascular depletion leading to hypoxic niche, drug resistance, and tumor recurrence rate or leading to impaired delivery of chemo drugs and immune cell infiltration at the tumor site. Achieving a balance between oxygenation and tumor growth inhibition requires determining vascular normalization after treatment with a low dose of antiangiogenic agents. However, monotherapy within the approved antiangiogenic agents’ benefits only some tumors and their efficacy improvement could be achieved using immunotherapy and emerging nanocarriers as a clinical tool to optimize subsequent therapeutic regimens and reduce the need for a high dosage of chemo agents. More importantly, combined immunotherapies and nano-based delivery systems can prolong the normalization window while providing the advantages to address the current treatment challenges within antiangiogenic agents. This review summarizes the approved therapies targeting tumor angiogenesis, highlights the challenges and limitations of current therapies, and discusses how vascular normalization, immunotherapies, and nanomedicine could introduce the theranostic potentials to improve tumor management in future clinical settings.